PENGATURAN HUKUM PERBATASAN NEGARA KESATUAN REPUBLIK INDONESIA BERDASARKAN UNDANG-UNDANG WILAYAH NEGARA - Manik, Jeanne Darc Noviayanti (Fakultas Hukum Universitas Bangka Belitung, 2018)
The arrangements area of the country is done to provide legal certainty and clarity to citizens on the territory of the country. Area of the country as outlined in the Constitution of the Republic of Indonesia Year 1945 has an arrangement the Government of Indonesia that protects the Nations Indonesia, the utilization of earth, water, and air as well as the natural resources contained therein for the most of people's prosperity, decentralization of Government to the areas large and small that are autonomous in the frame of the unitary State of the Republic of Indonesia; and social welfare for all the people of Indonesia.